Early sepsis does not stimulate reactive oxygen species production and does not reduce cardiac function despite an increased inflammation status. Issue 13 (12th July 2017) - Léger, Thibault; Charrier, Alice; Moreau, Clarisse; Hininger‐Favier, Isabelle; Mourmoura, Evangelia; Rigaudière, Jean‐Paul; Pitois, Elodie; Bouvier, Damien; Sapin, Vincent; Pereira, Bruno; Azarnoush, Kasra; Demaison, Luc
Abstract: If it is sustained for several days, sepsis can trigger severe abnormalities of cardiac function which leads to death in 50% of cases. This probably occurs through activation of toll‐like receptor‐9 by bacterial lipopolysaccharides and overproduction of proinflammatory cytokines such as TNF‐ α and IL‐1 β . In contrast, early sepsis is characterized by the development of tachycardia. This study aimed at determining the early changes in the cardiac function during sepsis and at finding the mechanism responsible for the observed changes. Sixty male Wistar rats were randomly assigned to two groups, the first one being made septic by cecal ligation and puncture (sepsis group) and the second one being subjected to the same surgery without cecal ligation and puncture (sham‐operated group). The cardiac function was assessed in vivo and ex vivo in standard conditions. Several parameters involved in the oxidative stress and inflammation were determined in the plasma and heart. As evidenced by the plasma level of TNF‐ α and gene expression of IL‐1 β and TNF‐ α in the heart, inflammation was developed in the sepsis group. The cardiac function was also slightly stimulated by sepsis in the in vivo and ex vivo situations. This was associated with unchanged levels of oxidative stress, but several parameters indicated a lower cardiac production of reactive oxygen species in the septic group. In conclusion, despite the development of inflammation, early sepsis did not increase reactive oxygen species production and did not reduce myocardial function. The depressant effect of TNF‐ α and IL‐1 β on the cardiac function is known to occur at very high concentrations. The influence of low‐ to moderate‐grade inflammation on the myocardial mechanical behavior must thus be revisited. Abstract : Early sepsis is accompanied by a loss of skeletal muscle mass and an activation of the inflammation process with increased plasma TNF‐ α concentration and cardiac expression of TNF‐ α and IL‐1 β RNAs. Despite the inflammation burst, the cardiac function is increased in the in vivo situation as well as ex vivo in the perfused heart. The improved cardiac function is associated with a lower reactive oxygen species production which can preserve the cellular energy metabolism.